Pengaruh Jumlah Produksi, Tenaga Kerja, dan Jam Kerja Terhadap Produktivitas di CV. XYZ - Ricky Arya Pratama; Siti Ning Farida (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the effect of production quantity, labor, and working hours on productivity at CV. XYZ, a chemical manufacturing company that operates as a sole supplier. This research uses a quantitative approach and is an associative research. The sampling technique used in this study was saturated sampling technique with a total sample size of 24 monthly production reports from 2020-2021. The data analysis technique used is multiple linear regression analysis using SPSS version 26. The results showed that simultaneously the amount of production, labor and working hours had a significant effect on productivity. Partially, the amount of production has a significant positive effect while labor, and working hours have a significant negative effect on productivity at CV. XYZ.